Geoelectric structure of the Dharwar Craton from magnetotelluric studies: Archean suture identified along the Chitradurga–Gadag schist belt - Gokarn, S. G.; Gupta, Gautam; Rao, C. K. (My University, 2004)
Broad-band magnetotelluric data were collected at 50 stations over a 400 km long, approximately east–west profile over the granite–greenstone terrain of Dharwar, southern India. The tensor decomposed data were interpreted using a 2-D inversion scheme. The geoelectric model is suggestive of a suture along the Chitradurga–Gadag schist belt, formed by the thrusting of the West Dharwar Craton beneath its eastern counterpart, with an easterly dip of 20–30°. The thrust proposed here pre-dates the formation of these schists, which occurred during the Late Archean (2600 Ma). The accretionary wedge of the thrust and the depressed part of the West Dharwar Craton may have controlled the emplacement of the Chitradurga–Gadag and Shimoga–Dharwar schists. The subsequent weathering, the several episodes of tectonic activity witnessed during the Precambrian and the vertical block movements caused during the passage of the Indian Plate over the Reunion hotspot may have modified the crust, leading to the present-day geological configuration. Despite its age and several tectonothermal episodes, the signature of this thrust is adequately preserved in the Dharwar Craton. Several similarities with younger sutures, as is evident from the observed relics of the oceanic rocks present along the Chitradurga schist belt, suggest that the tectonic processes leading to this Archean event may have had a close resemblance to those witnessed in recent times. Magnetotelluric studies also image a zone of low resistivity at a depth of 40 km beneath the west Dharwar Craton. This seems to be a regional feature, extending to the north over a distance of at least 250 km beneath the Deccan volcanics. The low heat flow values and the high density associated with this feature make partial melting an unlikely explanation for the low resistivity. The grain boundary graphites and the sulphides deposited in the form of pyrites may have caused the low resistivity in the lithospheric mantle of the West Dharwar Craton, although the fluids generated and trapped in the mantle during the passage of the Indian Plate over the Reunion hotspot in the waning phase of its outburst could also be a possibility. The asthenosphere is delineated at a depth of about 100 km beneath the East Dharwar Craton.
Keywords: Archean suture; Archean tectonics; Dharwar craton; Magnetotellurics; South Indian Shield; Magnetotelluric data; Magnetotelluric studies; Gadag schist belt